Spirit Possession in Jesus Research - Craffert, Pieter F. (Religion & theology, 2018)
Except for demon possession, possession is a neglected and under-researched topic in New Testament studies in general and Jesus research in particular. That is unlike scholars from other disciplines who realise that spirit possession is a central feature in the emergence and growth of most religious traditions. This article first explains possession as a complex neurocultural phenomenon that is widely distributed in human societies where they fulfil a range of functions. It secondly introduces the anthropological study of possession in order to show that it cannot be invoked uncritically. The anthropological study of possession contains a range of theoretical perspectives on possession which needs to be accounted for in the cross-cultural appropriation of such research. Possession is described as the culturally appropriated practice of a common neurobiological propensity at dissociation. It is suggested that such experiences and practices were common in the world of Jesus and need to be recovered as one of the roots of the emergence of the Jesus movements.